Incorporating Network Communication and Sports Psychology: An In-depth Quantitative Analysis of Interdisciplinary Knowledge Graphs and Association Patterns in Chinese Sports News Communication - Zhendong Pan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the rapidly evolving landscape of sports news and sports psychology, driven by the proliferation of mobile Internet and Internet media in China, it is essential to recognize two pivotal factors shaping the discourse. Firstly, there is the imperative 'construction of new liberal arts' within professional knowledge education. Secondly, the practice of news communication is undergoing transformative changes due to media integration, particularly in the context of sports news concerning Chinese athletes. These two dynamics together create a favorable environment, underpinned by robust policy support, for interdisciplinary research at the intersection of sports psychology and sports news communication. Within the academic realm, our efforts must be attuned to the evolving curriculum and the unique challenges posed by this dynamic landscape. Such an approach is instrumental in advancing in-depth interdisciplinary research at the confluence of sports psychology and the communication of sports news. Recent years have witnessed an upsurge in research interest in media communication, with a pronounced emphasis on sports. In light of this, we have a unique opportunity to conduct a comprehensive analysis of interdisciplinary interactions within the domain of sports news and sports psychology. To facilitate this, we propose employing advanced knowledge graph techniques and correlation analysis. In this specialized context, the interdisciplinary study of sports psychology and sports news communication can be envisaged as a dynamic process that involves the assimilation and dissemination of specialized knowledge. We advocate for the application of a network environment correlation analysis method rooted in knowledge mapping principles. This approach entails the development of a tailored knowledge map specific to the realm of sports news concerning Chinese athletes, within the framework of sports psychology. Furthermore, we will explore the creation of efficient storage and retrieval mechanisms to optimize the effectiveness of our research pursuits in this exciting and evolving field.